A morphometric study of dry adult human sacra and its clinical relevance - Farhat, Rizwana; Priyanka (International Journal of Research in Medical Sciences, 2026)
Background: The sacrum shows considerable anatomical variability, particularly in relation to the sacral hiatus and sacral canal. These variations are clinically important, as they may influence the success and safety of procedures such as caudal epidural anaesthesia, spinal interventions and pelvic surgeries. Detailed morphometric data are therefore essential for improving procedural accuracy and reducing complications. The present study aimed to evaluate the morphometric parameters of the sacrum, with special emphasis on the sacral hiatus and its relationship to the second sacral foramen and to assess their clinical significance. Methods: The descriptive osteological study was conducted on fifty dry adult human sacra of unknown sex obtained from the Department of anatomy, and ESIC Medical College and Hospital, Faridabad, Haryana from May 2023 to December 2023. Measurements recorded included the length and anteroposterior diameter of the sacral hiatus, intercornual distance, the median distance between the lower margin of the S2 foramen and the apex of the sacral hiatus and the distance between the midpoint of the base of the hiatus and the S2 foramen. Data were analysed using descriptive statistics. Results: Considerable variation was observed in all morphometric parameters, with specific ranges predominating for each measurement. In the present study, the length of the sacral hiatus most commonly ranged between 11–20 mm (44%). The anteroposterior diameter of the sacral canal at the level of the hiatus was predominantly 4–6 mm in 72% of specimens. The intercornual distance at the base of the sacral hiatus most frequently measured between 11–15 mm. Such variations highlight differences in sacral anatomy among individuals. Conclusions: The study demonstrates significant morphometric variability of the sacrum, which has important clinical implications. Awareness of these variations can aid clinicians in improving the safety and success of caudal epidural anaesthesia and other sacral procedures, while also contributing valuable data for surgical planning and forensic identification.